Drill Based Model of Forehand Drive Practice in Table Tennis for Beginner Athlete (Department of Physical Education, Sport, Health and Recreation, 2020)
The purpose of study was to develop drill based model of forehand drive practice in table tennis for beginner athlete. The forehand drive had important role in table tennis playing. Forehand is a way to do a punch when hitting the ball the position of the palm holding the bet is facing forward. This research is development research using Research and Development from Borg and Gall which consists of ten stages. The subject in this research was beginner athlete at PTM Gajah Mada Medan. Data were collected through documentation, observation, interview and test of forehand drive in table tennis. Data analysis used qualitative and quantitative. The results of finding show that there are 24 items of drill model in forehand drive practice. The variety of practice table tennis were shadow ball, rolling ball, multiball MP, and multiball DP. It gave the impact on beginner athlete skills. They can be played the table tennis using forehand drive practice.